Cover Image. Issue 8 (8th July 2019) - Wang, Yu; Deng, Yeqiang; Liu, Yilu; Qu, Lu; Wen, Xishan; Lan, Lei; Wang, Jian
Abstract : The cover image is based on the Research Article Influence of blade rotation on the lightning stroke characteristic of a wind turbine, by Yu Wang et al., https://doi.org/10.1002/we.2341 . Cover image © Yu Wang, Yeqiang Deng, Yilu Liu, Lu Qu, Xishan Wen, Lei Lan, Jian Wang.